Imidacloprid Induced Toxicity In Ovary Of Female Wistar Rats In Two Generations (Applied Biological Research, 2018)
In present study the effect of oral administration of imidacloprid over two  generations on the ovary of female Wistar rats was assessed. Female rats were  divided into 3 groups. Group 1, as control, was given corn oil only while  imidacloprid was administered in group 2 and 3 @ 10 and 20 mg kg-1 bw day 1, respectively. A disruption in estrous cyclicity was observed with a prolonged  diestrous in both F1 and F2 generation. The weight of ovary decreased  significantly in treated female rats of F2 generation. Histopathology of ovary of  groups 2 and 3 revealed different stages of follicles. Percentage atresia of  follicles was found higher in treated rat ovaries as compared to their respective  control rats in both the generations. The results indicate that no observed effect  level of imidacloprid for two generations female reproductive toxicity is 10 mg kg-1 bw day-1.
Keywords: Histopathology; imidacloprid; ovary; phosphatases; rat